Healthy Community Movement (GERMAS) And Distance, Wearing Mask, And Washing Hands (3m) In the Elderly to Prevent the Spread of Covid 19 - Endrian Mulyady Waluyo (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Healthy community movement (GERMAS) and social distancing, wearing masks, and handwashing (3M) are important points in preventing the spread of covid 19. Problems in the fort village have problems around the elderly, especially hypertension and rheumatic diseases. Then distrust of the covid 19 vaccine and poor waste management. The priority of partner problems is firstly the problems surrounding elderly diseases, especially hypertension and rheumatism. The second problem is the distrust of covid 19 vaccination. The third is bad waste management. But the priority in this article is the problem of groups vulnerable to the spread of covid, namely the elderly. Based on the agreement with partners, the priority is the problem of preventing the spread of covid 19 in the elderly by emphasizing the strengthening of the community movement for a clean and healthy living than the addition of the 3M protocol (Wearing masks, Keeping a distance, and Washing hands in Ciamis Regency. The counseling method uses leaflets and video media, There were 20 elderly correspondents. The results showed an increase in knowledge from the mean pre-test of 70 to 90. Conclusion Leaflet and video media can be used in counseling to have a significant impact on knowledge.